2018
DOI: 10.1002/ejoc.201800659
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Trifluoromethylated Morpholines through Cascade Reactions of Bromoenones with Secondary Amino Alcohols

Abstract: Fluorinated α‐bromoenones react readily with amino alcohols containing a secondary amino group to give monocyclic morpholine derivatives or unexpected bicyclic compounds containing a morpholine moiety fused with an oxetane ring. The reactions are highly stereoselective. The assembly of these heterocycles starts with an aza‐Michael addition followed by intermolecular substitution and addition processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…: m/z (%) = 390 (100, M + ), 360 (37), 344 (19), 332 (19), 314 (14), 299 (12), 298 (61), 297 (37), 286 (22), 285 (12), 176 (11), 127 (10), 115 (14), 103 (10), 102 (36), 101 (20), 100 (13), 77 (15), 76 (36), 75 (33), 74 (14), 69 (33), 63 (11), 51 (24), 50 (24), 44 (48), 43 (14).…”
Section: Ms (Ei)mentioning
confidence: 99%
See 1 more Smart Citation
“…: m/z (%) = 390 (100, M + ), 360 (37), 344 (19), 332 (19), 314 (14), 299 (12), 298 (61), 297 (37), 286 (22), 285 (12), 176 (11), 127 (10), 115 (14), 103 (10), 102 (36), 101 (20), 100 (13), 77 (15), 76 (36), 75 (33), 74 (14), 69 (33), 63 (11), 51 (24), 50 (24), 44 (48), 43 (14).…”
Section: Ms (Ei)mentioning
confidence: 99%
“…The trifluoromethyl(-bromalkenyl)ketones are valuable templates for the assembly of fluorinated aza-heterocycles. Previously, we successfully used these bromoenones in the preparation of trifluoromethylated piperazin-2ones, 17 piperazines and morpholines condensed with aziridines, 18 unusual morpholines condensed with oxetanes or oxiranes, 19 bis-oxazines, 20 and other heterocycles. The most remarkable achievements of our research team in the synthesis of fluorinated aza-heterocycles were recently reviewed.…”
mentioning
confidence: 99%
“…The conjugate nucleophilic addition to functionalized enones is a straightforward method for the carbon–carbon or carbon–heteroatom bond formation. In this context, we recently demonstrated that trifluoromethylated α‐bromoenones are excellent Michael acceptors and valuable starting materials in the reaction with nitrogen‐bearing mono‐ or binucleophiles for assembly of a diversity of trifluoromethylated linear as well as carbo‐ and heterocyclic derivatives . These enones are ambivalent bielectrophiles bearing electrophilic centers at the carbonyl function and at the olefinic β‐carbon; therefore, they can react with nucleophiles either in 1,2‐ or 1,4‐addition mode.…”
Section: Introductionmentioning
confidence: 99%